2016
DOI: 10.1016/j.lfs.2016.02.041
|View full text |Cite
|
Sign up to set email alerts
|

GPER is required for the age-dependent upregulation of the myocardial endothelin system

Abstract: Aims Cardiac aging is associated with progressive structural changes and functional impairment, such as left ventricular hypertrophy, fibrosis and diastolic dysfunction. Aging also increases myocardial activity of endothelin-1 (ET-1), a multifunctional peptide with growth-promoting and pro-fibrotic activity. Because the G protein-coupled estrogen receptor (GPER) regulates vascular responsiveness to ET-1, we investigated whether GPER also plays a role in the regulation of the cardiac endothelin system with agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…In 2006, I was contacted by and soon (in 2008) met Matthias Barton at a drug discovery meeting in Dubai, beginning a more than 10-year collaboration [70, 132-147]. Various combinations of these individuals (along with superb graduate students, post-docs and technicians) would be central to our studies over the years to demonstrate that 1) GPER-expressing cells exhibited binding of a fluorescent estrogen derivative that colocalized with GPER to intracellular membranes (endoplasmic reticulum and Golgi apparatus) (Arterburn, Sklar, [66]); 2) only cell permeable estrogen derivatives rapidly activate GPER, suggesting intracellular GPER is functionally active (Arterburn, [99]); 3) GPER-selective agonists and antagonists, that do not interact with the classical estrogen receptors, can be identified (Oprea, Sklar, Arterburn, [85, 86, 148, 149]); 4) GPER can be visualized in vivo through the use of novel radio-imaging agents (Arterburn, [150-155]); 5) using murine models, including GPER knockout mice, GPER plays important roles in both breast and endometrial cancer (but not uterine imbibition for example) (Hathaway, [86, 156-158]) as well as in metabolism (Hathaway, [159]) and vascular biology and disease (Barton, [70, 134, 139-142, 145-147, 160, 161]); 6) GPER is prognostic for survival in both endometrial and ovarian cancers (Smith, [129, 130]) and 7) GPER is critical in aging through its regulation of superoxide production via Nox1 (Barton, [162]). Our work to understand the roles of GPER in metabolism [163] and vascular biology [71] and the potential clinical benefits of GPER-selective agonists and antagonists [149] are reviewed elsewhere in this special issue.…”
Section: Pharmacology and Physiology Of Gpermentioning
confidence: 99%
“…In 2006, I was contacted by and soon (in 2008) met Matthias Barton at a drug discovery meeting in Dubai, beginning a more than 10-year collaboration [70, 132-147]. Various combinations of these individuals (along with superb graduate students, post-docs and technicians) would be central to our studies over the years to demonstrate that 1) GPER-expressing cells exhibited binding of a fluorescent estrogen derivative that colocalized with GPER to intracellular membranes (endoplasmic reticulum and Golgi apparatus) (Arterburn, Sklar, [66]); 2) only cell permeable estrogen derivatives rapidly activate GPER, suggesting intracellular GPER is functionally active (Arterburn, [99]); 3) GPER-selective agonists and antagonists, that do not interact with the classical estrogen receptors, can be identified (Oprea, Sklar, Arterburn, [85, 86, 148, 149]); 4) GPER can be visualized in vivo through the use of novel radio-imaging agents (Arterburn, [150-155]); 5) using murine models, including GPER knockout mice, GPER plays important roles in both breast and endometrial cancer (but not uterine imbibition for example) (Hathaway, [86, 156-158]) as well as in metabolism (Hathaway, [159]) and vascular biology and disease (Barton, [70, 134, 139-142, 145-147, 160, 161]); 6) GPER is prognostic for survival in both endometrial and ovarian cancers (Smith, [129, 130]) and 7) GPER is critical in aging through its regulation of superoxide production via Nox1 (Barton, [162]). Our work to understand the roles of GPER in metabolism [163] and vascular biology [71] and the potential clinical benefits of GPER-selective agonists and antagonists [149] are reviewed elsewhere in this special issue.…”
Section: Pharmacology and Physiology Of Gpermentioning
confidence: 99%
“…In this sense, some authors found a link between ET-1 and aging-related cardiac fibrosis; Wang et al demonstrated that ET-1 increased FN and collagen expression in cardiac fibroblast, and hearts from old mice showed cardiac fibrosis with upregulation of ET-1 [26]. Meyer et al observed that aging increased mRNA myocardial expression of ECE-1 and ET receptors in mice, which could be associated with heart failure, fibrosis and left ventricular hypertrophy [56]. According to this data, the fibrosis we found in the gastrocnemius and tibialis anterior muscles from old mice could explain at least in part the reduction in muscle force.…”
Section: Agingmentioning
confidence: 99%
“…Similarly, isolated carotid arteries from GPER null mice had augmented contractile responses to ET‐1, indicating that endogenous GPER dulls the vasoconstrictive response to ET‐1, an effect that may be due to decreased sensitivity of contractile machinery to Ca 2+ release in VSMCs (Meyer et al ., ). Additionally, GPER −/− mice do not exhibit an increase in ET B receptors and endothelin‐converting enzyme (ECE)‐2 in the ageing myocardium, ET system components, which may be associated with heart failure and hypertrophy in older animals (Meyer et al ., ). Interestingly, there is also evidence that ET‐1 increases mRNA expression of GPER and that GPER is necessary for some downstream actions of ET‐1 in SKBR3 and HepG2 cell lines (Bartella et al ., ).…”
Section: G Protein‐coupled Oestrogen Receptormentioning
confidence: 97%